2001
DOI: 10.1086/319855
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 (HIV‐1) Plasma Virus Load and Markers of Immune Activation among HIV‐Infected Female Sex Workers with Sexually Transmitted Diseases in Abidjan, Côte d'Ivoire

Abstract: Plasma levels of human immunodeficiency virus type 1 (HIV-1) RNA and markers of immune activation were compared among HIV-1-infected female sex workers (FSWs) with (n=112) and without (n=88) sexually transmitted diseases (STDs) in Abidjan, Côte d'Ivoire. After adjustment for CD4+ T cells, the median virus load was 2.5-fold higher among HIV-seropositive FSWs with STDs than among those without an STD (P=.053). Median virus load was higher for FSWs with a genital ulcer (P=.052) or gonorrhoea (P=.058) than for FSW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…It has been reported that with respect to the effects of individual STDs on HIV load, only genital ulcers and gonococcal infection are associated with higher viral load. Chlamydia, which is very close to GC in terms of infectious properties, does not enhance HIV load (64). We did not examine the specificity of GC to HIV infection of DCs.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that with respect to the effects of individual STDs on HIV load, only genital ulcers and gonococcal infection are associated with higher viral load. Chlamydia, which is very close to GC in terms of infectious properties, does not enhance HIV load (64). We did not examine the specificity of GC to HIV infection of DCs.…”
Section: Discussionmentioning
confidence: 95%
“…Staining and analysis were performed in phosphate-buffered saline (PBS) with 1% fetal calf serum (FCS). For intracellular perforin analyses, after surface-marker labeling, cells were fixed and permeabilized with PermeaFix (Ortho Diagnostic Systems, Raritan, NJ) before intracellular staining with antiperforin monoclonal antibody (27)(28)(29)(30)(31)(32)(33)(34)(35); BD PharMingen). Isotype-matched controls were used for both surface and intracellular staining.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Symptomatic Ng infection is associated with increased detection of viral-derived nucleic acids from genital secretions of men and women (11)(12)(13), and this effect was reversed upon successful Ng treatment. Concurrent Ng infection is associated with an increase in HIV-1 viremia (14,15), decreases in HIV-1 target lymphocyte [cluster of differentiation 4-positive (CD4 + ) T-cell] counts (14), and a decrease in effector [cluster of differentiation 8-positive (CD8 + ) T-cell] lymphocyte responses (16). Because of the impact of Ng on HIV-1 shedding, coinfection is associated with a two-to fivefold increase in male-to-female transmission rates (3).…”
mentioning
confidence: 99%